BNP was Associated with Ischemic Myocardial Scintigraphy and Death in Patients at Chest Pain Unit - Azevedo,Jader Cunha de (2015)
Background:Recent studies have suggested that B-type Natriuretic Peptide (BNP) is an important predictor of ischemia and death in patients with suspected acute coronary syndrome. Increased levels of BNP are seen after episodes of myocardial ischemia and may be related to future adverse events.Objectives:To determine the prognostic value of BNP for major cardiac events and to evaluate its association with ischemic myocardial perfusion scintigraphy (MPS).Methods:This study included retrospectively 125 patients admitted to the chest pain unit between 2002 and 2006, who had their BNP levels measured on admission and underwent CPM for risk stratification. BNP values were compared with the results of the MPS. The chi-square test was used for qualitative variables and the Student t test, for quantitative variables. Survival curves were adjusted using the Kaplan-Meier method and analyzed by using Cox regression. The significance level was 5%.Results:The mean age was 63.9 ± 13.8 years, and the male sex represented 51.2% of the sample. Ischemia was found in 44% of the MPS. The mean BNP level was higher in patients with ischemia compared to patients with non-ischemic MPS (188.3 ± 208.7 versus 131.8 ± 88.6; p = 0.003). A BNP level greater than 80 pg/mL was the strongest predictor of ischemia on MPS (sensitivity = 60%, specificity = 70%, accuracy = 66%, PPV = 61%, NPV = 70%), and could predict medium-term mortality (RR = 7.29, 95% CI: 0.90-58.6; p = 0.045) independently of the presence of ischemia.Conclusions:BNP levels are associated with ischemic MPS findings and adverse prognosis in patients presenting with acute chest pain to the emergency room, thus, providing important prognostic information for an unfavorable clinical outcome.